2014
DOI: 10.14219/jada.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of implants and restorations placed in general dental practices

Abstract: Objectives The authors conducted a study to determine the types, outcomes, risk factors and esthetic assessment of implants and their restorations placed in the general practices of a practice-based research network. Methods All patients who visited network practices three to five years previously and underwent placement of an implant and restoration within the practice were invited to enroll. Practitioner-investigators (P-Is) recorded the status of the implant and restoration, characteristics of the implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 27 publications
7
16
4
1
Order By: Relevance
“…The age range of patients (19 years to 76 years) in this study is similar to that reported in a previous Nigerian study [2] and an Australian study [12]. The mean (standard deviation) age of the patients 50.08±13.54 years noted in this study is close to the 51.5years reported in Australia [12] but lower than the 61.4±12.2 years and 60.6±12.7 years recorded in previous studies [10,13] and higher than the 48.4±16.6 years recorded in a previous Nigerian study [2]. The most prevalent age group was 41-50years in this study, a finding different from the most prevalent age group of 60-69years reported in previous studies [12,14].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The age range of patients (19 years to 76 years) in this study is similar to that reported in a previous Nigerian study [2] and an Australian study [12]. The mean (standard deviation) age of the patients 50.08±13.54 years noted in this study is close to the 51.5years reported in Australia [12] but lower than the 61.4±12.2 years and 60.6±12.7 years recorded in previous studies [10,13] and higher than the 48.4±16.6 years recorded in a previous Nigerian study [2]. The most prevalent age group was 41-50years in this study, a finding different from the most prevalent age group of 60-69years reported in previous studies [12,14].…”
Section: Discussionsupporting
confidence: 87%
“…More patients are becoming aware of the use of dental implant as a form of tooth replacement therapy as a result of the unlimited information from the web and this has increased the demand for dental implants [9]. Implant therapy although accepted as a predictable treatment option for replacing missing teeth [10] is still yet to be a readily available treatment in developing economies like Nigeria. Some studies have been done in this clime as regard implant treatment of patients with good outcome [2,11] however, these studies were done majorly in the South western region, there still appears to be paucity of studies in other regions hence the need for this study which characterised the types of implants and implant supported restorations placed in a tertiary hospital in the Federal Capital Territory (FCT) of Nigeria as well as determine the outcome of the implant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Implants are regarded as a failure if it is removed for any reason, with clinical mobility being an absolute indication for their removal. Survival indicates that the implants are present in the oral cavity and functioning [ 1 ], with the survival rate reported to be around 95.5–97.8%. Implants in the survival category achieve success if they meet specific criteria, including a lack of biologic and/or technical complications [ 1 ], achieving an adequate amount of keratinized mucosa and soft tissue coverage, and patient satisfaction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported high rates of survival, many surviving implants were categorized as failures (19%–64%) depending on applied success criteria29. Surgical extrusion is likely to be more cost-effective than a single-implant-supported restoration30.…”
Section: Discussionmentioning
confidence: 99%